Pengaruh Regret Aversion Bias dan Risk Tolerance bagi Investor Muda Jawa Barat terhadap Keputusan Investasi - Wahyu Nurdinda; Asep Muslihat; Raden Aditya Kristamtomo Putra (AKUNSIKA: Jurnal Akuntansi dan Keuangan, 2020)
This study aims to describe the influence of regret aversion bias and risk tolerance on west java young investors through investment decision partially and simultaneously. Data obtained by distributing questionnaires in 8 State Universities in West Java with sample of 363 people taken from grade 2015 of Economics and Business Faculty students. After the data is obtained, then the data is analyzed using the path analysis. The results of the verification test showed regret aversion bias partially has total influence 7% on investment decision while risk tolerance partially has total influence 22,8% on investment decision, finally total influence of regret aversion bias and risk tolerance on investment decision simultaneously is equal 29, 8% and the influence of other variables outside the model is 70.2%..